A pilot study of Telco’s next generation IT architecture evolution: business function virtualization (BFV) - Wen QIAO; Xiaozheng WANG; Zhenqiang SUN; Gan REN; Yunxin LIU; Aidong YANG; Peng WANG; Da WANG; Xiaozhou YE; Ye OUYANG (Dianxin kexue)
With the development of information and communication technologies, traditional telecom business support systems (BSS) are facing the challenge of agilely meeting the flexible needs from business.Application scenarization, service standardization, technology componentization and resource sharing have gradually become the consensual features among the evolution of telecom BSS architectures.A business function virtualization (BFV)-based BSS architecture, which is based on cloud-native, micro-services, containers, and DevOps technologies, was proposed.By embedding four components into the architecture, including standardized virtual network functions, modular design orchestrator, micro-service management framework, and multi-plane elastic computing controller, the system is able to deploy unitized system and distributed cloud.Therefore, the requirements of flexible telecom business development and frequent evolution of the system could be satisfied by the proposed BFV-based BSS architecture.In other words, the lightweight delivery of IT technologies and agile business support could be fulfilled by using the proposed BFV-based BSS architecture, and the proposed architecture will eventually become the standard architecture of next generation telecom BSS.